Global Reduction in HIV-related Maternal Mortality: ART as a Key Strategy - Hamisu M. Salihu, MD, PhD (Global Health and Education Projects, Inc., 2016)
Dr. Holtz and colleagues present a synthesis of evidence from published studies over the previous decade on the collective impact of HIV-targeted interventions on maternal mortality. Amongst an assortment of interventions [that include antiretroviral therapy (ART), micronutrients (multivitamins, vitamin A and selenium), and antibiotics], only ART reduced maternal mortality among HIV-infected pregnant and post-partum mothers. These ﬁ ndings have fundamental and global strategic implications. They are also timely since they provide the evidence that ART reduces HIV-related maternal mortality, and by further enhancing access to ART in HIV-challenged and poor regions of the world, signiﬁ cant improvement in maternal morbidity and mortality indices could be attained. The paper bears good tidings and sound scientiﬁ c proof that the ﬁ nancial investment made globally by government and non-governmental organizations and agencies to reduce the global burden of HIV/AIDS primarily by making ART more accessible to regions of the world most affected by the epidemic is beginning to show beneﬁ cial effects not only in terms of numerical reductions in the rates of new cases of HIV/AIDS among women, but also in maternal mortality levels. Key words: Maternal mortality • HIV-related maternal mortality • Pregnant mothers • Post-partum mothers • HIV-targeted interventions • Anti-retroviral therapy • Systematic review Copyright © 2015 Salihu. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.